Effects of silvicultural treatment on the stability of black pine plantations. - Cantiani, Paolo; Plutino, Manuela; Amorini, Emilio (Annals of Silvicultural Research, 2026)
Black pine plantations have been established at the purpose of recovering a forest cover to marginal soils, mostly throughout the Apennines range in Italy, since the end of the eighteenth century and up to the mid 1900. Both the decay of forest cover and soil erosion were the outcome of the long-lasting overuse through the intensive forest exploitation practices, grazing of the forest floor and wildfires, occurring since many centuries ago. The primary function of pine reafforestation was therefore to re-establish a first cover with a pioneer species, preparatory to future mixed forest types based on the natural reintroduction of broadleaves originally living in the same areas, mainly deciduous oaks and beech in the upper part. These goals have been partly met over the wide reafforestation area; the key functions of pine stands are today the protection against soil erosion and the hydrological regulation of catchments. The pine stands have been assuming today also a scenic role because they have been incorporated in the landscape physiognomy. A series of thinning up to the regeneration phase had been planned by foresters since the design of these plantations, but many stands have grown unthinned and fully stocked for a long time, this condition contributing a less mechanical stability of trees. Alternative forms of regeneration in grown-up stands have been and are being tested to improve both the natural and artificial establishment of indigenous species, but thinnings remain, even if a tardy measure, the main practice enforceable to these pine forests. The results of experimental trials undertaken in the black pine forest stand located in Pratomagno casentinese (Arezzo) are being reported in the paper. The study started in 1978 and the following theses were tested (A) heavy thinning from below; (B) moderate thinning from below; (C) control. Three thinnings were carried out in 1978, 1999 and 2009 at the ages of 24, 45 and 55. The action over time of each intervention on the mensurational and mechanical stability parameters (H/D ratio H/Ddom ratio), are being analyzed. The stability parameters of the pine forest after three interventions (H/D ratio, crown ratio, horizontal crown projection and eccentricity of the crown) have been also analyzed on a sample of trees per thesis and compared with those of trees grown in absence of competition. Sampled trees were sorted per social class. Results proved that type, interval and intensity of thinning related to the age of intervention are the main determinants of a successful treatment. Thinnings from below increase individual stability over time only when also trees living in the main crop layer are being removed. The trials showed the improvement of stability parameters following the intermediate thinning applied at the age of 45. The thesis of heavy thinning had the best performance as for the awaited purpose. <!–[if gte mso 9]> <![endif]–><!–[if !mso]> <![endif]–><!–[if gte mso 10]> <![endif]–>